Rancang Bangun Aplikasi Pencatatan Penjualan Suku Cadang dan Jasa Service Motor Berbasis Desktop Pada PT. AS MOTOR - Purwanto Purwanto; Erwin Sutomo; Rudi Santoso (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The process of recording the sale of spare parts and services, the service motor that includes the company's interaction to the customer and internal interactions between parts of the PT. As Motor not computerized. The problem that exists is in the process of identifying damage to vehicle in which the mechanics are not doing service in accordance with the standard operating procedure as well as the mechanics are working on improvements often work vehicle repair other customers and service advisors are not directly know the stock of spare parts that exist when the sales of spare parts, the impact is disturbing the development and progress of the workshop.The solution to solve the problem is an application that can automate customer interactions to the company and the interaction between the internal parts is to design and build applications recording sales of spare parts and services, the service -based motor desktop. These applications generate sales reports information in the form of spare parts, spare parts sales reports per period, circulation reports sales of spare parts, service revenue reports per mechanics, spare parts inventory reports, and reports the purchase of spare parts. Keywords: Spare Parts, Service Fees, Sales, Desktop Based Application.